HARMONISASI MAKEUP SOFT GLAM DENGAN PAES SOLO PUTRI PADA RIAS PENGANTIN - Zdihni Zalfa Afrillia; Sabila Mutiara Ningrum; Nadya Agustina Tiara Santi; Pramesti Adika Ratri; Primananda Suryani (STKIP Subang, 2026)
This study aims to analyze the process of harmonizing soft glam makeup with the Solo Putri paes in bridal makeup, as a response to shifting global beauty trends that favor a more natural look without compromising traditional values. In order to investigate the subjective experiences, aesthetic concerns, and creative processes of wedding makeup artists, the research uses a qualitative method with a phenomenological design. Direct observation, in-depth interviews, and documentation with participants, teachers, and makeup artists at LKP Puspa Patra Kembala and Bening Beauty Makeup were among the methods used to gather data. Thematic analysis was used to find important themes and patterns in the data.Five major themes emerged from the findings: (1) skin texture control as a technical foundation, (2) the application of layering techniques to ensure makeup longevity, (3) the creation of flexible facial dimensions, (4) the precise execution of paes according to established norms, and (5) the blending of classic and contemporary design. The results show that the capacity to maintain the paes' symbolic structure as the main component is what makes this harmonization successful, with the soft glam method acting as a supporting factor for visual attractiveness. The idea of integrating contemporary methods with traditional values in wedding makeup is strengthened by this research. In general, makeup artistry necessitates striking a balance between technical proficiency, cultural awareness, and creative aesthetics. This research has important ramifications for professional practice, cultural preservation initiatives, and the creation of cosmetics education programs. It is advised that further study be done to look at service users' viewpoints and do a more thorough visual analysis.